Somatosensory cortical activation in cervical dystonia and its modulation with botulinum toxin: an fMRI study - Opavský, Robert; Hluštík, Petr; Otruba, Pavel; Kaňovský, Petr (International Journal of Neuroscience, 2012)
Converging data on focal dystonias suggest a widespread disorder of somatosensory processing. The aims of our study were, first, to assess somatosensory activation patterns in cervical dystonia (CD) beyond the representation of the affected body parts and, second, to search for task-related activation changes induced by botulinum toxin type-A (BoNT-A) therapy. Functional magnetic resonance imaging (MRI) during electrical median nerve stimulation was employed in seven CD patients and nine controls; the examination was repeated 4 weeks after BoNT-A application to dystonic neck muscles. The pretreatment activation map of patients showed activation in the contralateral primary somatosensory cortex, but missing activation in the secondary somatosensory cortex and insula, in contrast to controls and patients after treatment. Clinically significant effect of BoNT-A therapy was associated with a significant increase of BOLD response in the contralateral secondary somatosensory, insular, and inferior parietal cortices. The posttreatment somatosensory maps of patients did not significantly differ from controls. This study has brought evidence of widespread disruption of somatosensory processing in CD and its modification with BoNT-A therapy.
Keywords: Somatosensory Disorders; Adult; Somatosensory Cortex; Male; lidé; lidé středního věku; Humans; krční svaly; Middle Aged; Botulinum Toxins, Type A; Neck Muscles; Torticollis; injekce intramuskulární; botulotoxiny typu A; mužské pohlaví; Neuromuscular Agents; somatosenzorické korové centrum; dospělí; nervosvalové látky; ženské pohlaví; tortikolis; somatosenzorické poruchy; Female; Injections, Intramuscular